STUDY OF SPECTRAL-LUMINESCENT AND PHOTOCHEMICAL PROPERTIES OF STYRYLSIANINE DYES - Tursunov, Shokir (Journal of Higher Education and Academic Advancement, 2024)
In this work, the relationship between the spectral-luminescent and photochemical properties of styrylcyanine homodimer dyes and the regularity of their specific electronic structure, the nature of their excited electronic state, and the processes of intermolecular interaction in solutions of the studied substances were calculated.